Elucidating colorectal cancer-associated bacteria through profiling of minimally perturbed tissue-associated microbiota - Fukuoka, Hironori; Tourlousse, Dieter M.; Ohashi, Akiko; Suzuki, Shinsuke; Nakagawa, Kazuya; Ozawa, Mayumi; Ishibe, Atsushi; Endo, Itaru; Sekiguchi, Yuji (Frontiers in Cellular and Infection Microbiology, 2023)
Sequencing-based interrogation of gut microbiota is a valuable approach for detecting microbes associated with colorectal cancer (CRC); however, such studies are often confounded by the effect of bowel preparation. In this study, we evaluated the viability of identifying CRCassociated mucosal bacteria through centimeter-scale profiling of the microbiota in tumors and adjacent noncancerous tissue from eleven patients who underwent colonic resection without preoperative bowel preparation. High-throughput 16S rRNA gene sequencing revealed that differences between on-and off-tumor microbiota varied considerably among patients. For some patients, phylotypes affiliated with genera previously implicated in colorectal carcinogenesis, as well as genera with less well-understood roles in CRC, were enriched in tumor tissue, whereas for other patients, on-and off-tumor microbiota were very similar. Notably, the enrichment of phylotypes in tumor-associated mucosa was highly localized and no longer apparent even a few centimeters away from the tumor. Through short-term liquid culturing and metagenomics, we further generated more than one-hundred metagenome-assembled genomes, several representing bacteria that were enriched in on-tumor samples. This is one of the first studies to analyze largely unperturbed mucosal microbiota in tissue samples from the resected colons of unprepped CRC patients. Future studies with larger cohorts are expected to clarify the causes and consequences of the observed variability in the emergence of tumor-localized microbiota among patients.